Training Ubudiyah Pada Anak Usia Dini Di Pondok Pesantren Putra Darul Qur’an Sumbersari-Kencong-Kepung-Kediri-Jatim - Muhammad Miftachul Aula; Doni Saputra (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
This Ubudiyah training has a point of emphasis on prayer and ablution activities at the Putra Darul Qur'an Islamic Boarding School, and knowing the various methods and media used in these activities. Prayer and ablution are obligatory and main things for people of the Islamic religion, because everyone who is Muslim must be able to pray. Therefore, prayer is very important to be introduced to early childhood. This study uses the Demonstration Method, which is a teaching method by demonstrating events, rules, and sequences of carrying out activities either directly or through the use of teaching media that are relevant to the subject or material being presented. Based on several references relevant to this study which have been analyzed by researchers, it can be concluded that Ubudiyah activities at the Putra Darul Qur'an Islamic Boarding School are very important and have an effect on early childhood.